INCOTERMS as a form of standardisation in international sales law : an analysis of the interplay between mercantile custom and substantive sales law with specific reference to the passing of risk - Coetzee, Juana (University of Stellenbosch, 2010)
International sales contracts have very specific needs that stem from the multiplicity of legal systems which apply to such contracts. In addition to harmonised law, mercantile custom is able to address many of these needs. Mercantile custom represents usages which are clear, certain and efficient and are expected to be known and applied by merchants in a particular trade or region. To this extent mercantile custom fulfils an automatic harmonisation function. However, where a custom does not enjoy uniform application across all branches of trade, the harmonisation function of mercantile custom is limited, as is the case with trade terms. Trade terms reflect mercantile customs and usages which developed over a long time in order to simplify the trade in goods that are transported from one place to the other. They regulate the delivery obligations of the seller and buyer as well as associated obligations such as the passing of risk. Trade terms negate the need for elaborate contract clauses and appear in abbreviated form in contracts of sale. Although they provide a uniform expression of mercantile custom in a particular location or trade, the understanding of trade terms tend to differ from country to country, region to region or from one branch of trade to the next. The ICC INCOTERMS is an effort to standardise trade term definitions at the hand of the most consistent mercantile customs and practices. The aim of this study is to investigate the efficiency of INCOTERMS as a form of standardisation in international sales law. For purposes of the investigation the focus is limited to the passing of risk. Although national laws usually have a default risk regime in place, merchants still prefer to regulate risk by means of trade terms. This study will investigate the legal position in the case of FOB, CIF and DDU terms. An analysis of the risk regimes of a few selected national systems will show that each has their own understanding of these trade terms. The United Nations Convention on Contracts for the International Sale of Goods (CISG) does not refer to trade terms, but many commentators have concluded that the CISG risk rule is consistent with INCOTERMS. The study will discuss this in more detail. To determine the efficiency of INCOTERMS as a form of standardisation in international sales law, the study examines their characteristics, legal nature as well as their limited scope of regulation. Specific emphasis is placed on the interplay between the CISG and INCOTERMS and the possibility of some form of interaction and collaboration between the two instruments. It is concluded that collaboration between INCOTERMS and the CISG adds value to the international law of sales by increasing the efficiency of an international business transaction and thereby facilitating international trade.
Keywords: CISG; INCOTERMS; Mercantile custom; Standardisation

International Investment Law and Media Disputes: A Complement to WTO Law - Peterson, Luke Eric (Transnational Corporations Review, 2010)
The recent high-stakes dispute between Google and China over censorship and cyber-security has spawned renewed discussion of the international trade law protections that internet and media companies may enjoy. Less recognized, however, is a perhaps more powerful legal tool in the arsenal of internet and media companies engaging in cross-border investments, namely international investment law.
Keywords: China; international investment; law; media

The participation of developing countries in the dispute settlement system of the WTO - Al. Shraideh, Saleh Adnan (Macquarie University, 2010)
International trade relations have become much more legalised under the World Trade Organization (WTO) than under the former international trade system created pursuant to the General Agreement on Tariffs and Trade (GATT). The Dispute Settlement Understanding (DSU) of the WTO clearly represents a shift toward a rule-oriented, legalistic and adjudicative approach, which is intended to enhance that status of, and confidence in, the WTO dispute settlement system. The approach is likely to ensure greater stability and predictability in the system by encouraging precise decisions on the merits of disputes and discouraging infractions. Its greater binding effect serves as a powerful disincentive to those Members who have a propensity to favour unilateral measures to solve international trade disputes. This is particularly beneficial for developing countries that sought a system which recognises their disadvantaged position compared to the greater bargaining and retaliatory power of developed countries. However, despite the positive assessment of the WTO dispute settlement system, the functioning of the system is working against the interest of developing countries in having an efficient dispute settlement system that considers their needs and deals fairly with their disputes. This thesis examines the participation of developing countries in the dispute settlement system of the WTO, and argues that they are in a disadvantageous position compared to their developed counterparts. The system's failure to effectively address or efficiently deal with this position is an evidence of its bias against and deficiency towards developing countries' participation. The thesis focuses on the problematic issues developing countries face throughout their use of the system. It also considers the role that the DSU has played in addressing these issues and the efficiency of that role in restraining and limiting their effect on developing countries' participation in the system. The thesis analyses some ideas on the reform of the DSU that have been proposed through WTO negotiations or literature, and discusses their applicability on the current dispute settlement system. Finally, the thesis employs these proposals along with its discussion on the subject to introduce a reformed model of the DSU which is more sensitive to developing countries' concerns in the system in order to help providing an understanding of how such modifications could be carried out in future reforms on the DSU.
Keywords: Conflict management; Developing countries; Foreign economic relations; GATT; General Agreement on Tariffs and Trade; International relations; Politics and government; WTO; World Trade Organization